Comparison of Self-Care Behavior through Diabetes Self-Care Management Education in Type 2 DM Patients in Urban And Rural - Rohani; Sri Handayani; Yusnaini (Universitas Ahmad Dahlan, 2023)
Background: Type 2 diabetes presents a significant global health challenge, with a key focus on patients' self-care behavior as integral to disease management. Empowering individuals through self-care management education is crucial for effective daily health management in Type 2 diabetes. This study aims to analyze the comparison of self-care practices through diabetes self-care management education in Type 2 DM sufferers in urban and rural areas. Methods: This study employs a quantitative approach with a cross-sectional design, involving 156 individuals with Type 2 diabetes. The participants are divided into 92 from Kutacane City and 64 from PuloKemiri Village, Babussalam District, Southeast Aceh Regency. Total sampling is utilized, encompassing the entire population based on specified inclusion criteria. The research utilizes the Summary of Diabetes Self-Care Activities (SDSCA) and diabetes self-care management educational material (DSME) as instruments, with data analysis conducted through the Independent Sample T-Test. Results: The research results showed that there were significant differences in self-care practices for Type 2 DM between individuals in urban and rural areas with a t-test value = 2.415 and a p-value of 0.013. Conclusion: Therefore, it is recommended that health workers adjust educational programs based on differences in needs and access to resources between the two groups.